Evaluation of Pregnancy Outcome of Placenta Previa in Aljala Maternity Hospital - Marwa Asid; Amel Morgham; Nasreen Osman; Karima Ali; Laylay Meeloud; Mohammed Sultan (AlQalam Journal of Medical and Applied Sciences, 2021)
Background and objective. Placenta Previa (PP) is associated with high demands on health care resources because it is a major cause of fetomaternal morbidity and mortality in developing countries. Complications include the potential for severe bleeding and preterm birth, as well as the need for cesarean delivery. This study aimed to determine prevalence, risk factors, and the adverse feto-maternal outcomes of placenta previa in Tripoli, Libya. Methods. A retrospective cohort study conducted using the maternal medical records from Aljalaa Maternity and Gynecology Hospital from January 2019 to December 2019. Results. One hundred twenty-eight patients enrolled in this study; their mean age were 28.6 ± 4.5 years (range: 20-38 years). Sixty-six (51.6%) of these pregnant women were multipara and 62 of them (48.4%) were primigravida. The frequency of PP was 1%. About 77 (60.2%) patients were had major PP, while 51 (39.8%) had minor PP. Approximately, 31/51(61%) of minor PP were nulliparous (primigravida). About 50% of patients with PP had previous caesarean section. 34/51(66.6%) patients with minor pp and 59/77(76.6%) patients of major pp presented with antepartum hemorrhage whereas the postpartum hemorrhage is documented only in 13.7% of minor pp patients and 7.8% of major pp patients. We found that 42.9% of the patients were O+ blood group, 38% either A+ or B+. Five (3.9%) patients (2 minor pp and 3 major pp) end by caesarean hysterectomy. Mortality rate was 3.9% (3 major pp and 2 minor pp). There were no differences between the major and minor pp groups, in term of history of evacuation and curettage, history of caesarean section, and interval between the last caesarean section and current pregnancy. Regarding neonatal outcome, no difference between groups regarding admission to NICU, sex of newborn, birth weight and Apgar score at 1 minute and 5 minutes (p> 0.05). Conclusion. The placental location may be an important determinant of pregnancy outcome. This study highlights the need for comprehensive obstetrics care and early identification of women at risk of placenta previa as it may help to prevent such complications.